THE EFFECT OF USING NESTED TYPE LEARNING MODEL ON UNDERSTANDING THE CONCEPT OF CLASS VII MTS IN ASHHABUL MAIMANAH - Roliyah, Roliyah; Kusuma, Jaka Wijaya; Nur, Maulida (Nindikayla Institute, 2023)
This research is motivated by the low understanding of students' mathematical concepts influenced by several things, one of which is the learning model used by the teacher. The teacher's selection of an inappropriate learning model will affect the student's learning process. Therefore, learning is needed to make it easier for students to understand mathematical concepts and involve them to be more active and concentrate more in the learning process. The research aims to determine: 1). Is the ability to understand the concept of students who are given learning with nested type models better than those given conventional learning; 2). How does using the nested type model affect the ability to understand the concepts of class VII MTS Ashhabul Maimanah? The method used in this study is the True experimental design method, posttest-only control design. Data collection techniques using students' mathematical concept understanding tests amounted to 8 items of description, and data analysis was carried out by testing requirements (normality test and homogeneity test), Hypothesis 1 Test (Average difference test), and Hypothesis 2 Test (Effect Size). Based on the t-test obtained = 2.8108 and = 1.1683. Because > so the decision is rejected and accepted. Based on the interpretation of the Cohens table in Table 1.7 with the 79th percentile in addition to the effect size, which is 0.882, this shows that the non-overlapping distribution of the experimental class scores with the control class score distribution of 47.7% is high. The conclusion is 1). Understanding the concept given by nested model learning is better than the conventional model. 2) The effect of using a nested learning model on the concept understanding of the seventh-grade students of MTS Ashhabul Maimanah is high.